Early Detection Behavior of Cervical Cancer Using Visual Inspection of Acetate (VIA) Method - Shinta Maya Sari; Asnawi Abdullah; Maidar Maidar (GLOBAL HEALTH SCIENCE GROUP, 2025)
The problem of early detection of cervical cancer using the Visual Inspection of Acetate (VIA) method in the Banda Aceh City Health Office work area is the low percentage of women aged 30-50 years who carry out early detection of cervical cancer using the VIA method. The purpose of this study was to analyze the behavioral factors of women aged 30-50 years who play the most crucial role in carrying out early detection of cervical cancer using the VIA method in the Banda Aceh City Health Office Work Area in 2021. This study is a quantitative study that is an analytical survey using the Case Control research method, a total sample of 360 women aged 30-50 years, namely: 180 Cases and 180 Controls (1: 1) by applying inclusion and exclusion criteria. The results of the multivariate analysis showed that there were factors that played the most crucial role in the behavior of carrying out early detection of cervical cancer using the VIA method in each variable model: Model 1 (predisposing factor) namely awareness P-value = 0.000, Model 2 (supporting factor) namely the availability of information P-value = 0.000, Model 3 (motivating factor) namely support from officers P-value = 0.000. The conclusion in the Final Model is that awareness is the main factor that plays the most crucial role with a P-value of 0.000 (OR: 54.1; 95% CI: 21.8–134.1), meaning that awareness behavior plays a 54 times greater role in women aged 30-50 years in carrying out early detection of cervical cancer using the VIA method in the Banda Aceh City Health Office Work Area in 2021.